Tissue Culture Derived Plantlet Variation in Caladium Humbolditi Schott (Journal of Science and Technology, 2016)
Callus cultures were initiated from corm and petiole explants of C. humboldtii on Murashige and Skoog's basal medium (MS) supplemented with 2,4-Dichlorophenoxyacetic acid (2,4-D) (0.4mg/l – 1.6mg/l) in combination with Kinetin (1mg/l) in the dark. Callus was induced on media supplemented with 0.8mg/l 2,4-Dichlorophenoxyacetic acid (2,4-D) in combination with kinetin (1mg/l) and callus induced on this media showed the best growth. Direct regeneration potential was higher in corm than in leaf explants. Regeneration was not achieved in petiole explants. De novo plant regeneration from callus cultures was not achieved and somatic embryogenesis did not yield any plantlets. Morphological differences were observed among the regenerated plantlets of C. humboldtii on Murashige and Skoog medium (MS) supplemented with 2,4-D (0.4mg/l) in combination with 1mg /l Kinetin. Polyacrylamide gel electrophoresis showed only 1 band each in the control and in the regenerants, however, the position of the bands were different. The result indicates that variation has occurred during in vitro culture. In conclusion, it has not been possible to generate plantlets from callus and it has also not been possible to advance the callus beyond the early stage of embryo development. The findings however include production of a new cultivar of C. humboldtii, initiation/growth of callus and direct regeneration of plantlets in the dark.